Apresiasi Sastra Akhir Pekan Berbasis Paguyuban Kelas Alternatif Untuk Meningkatkan Karakter Siswa Di SD Pertiwi Makassar - Hasliah Hasliah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This research is motivated by the fact that until now, literary appreciation learning in schools is still very concerning and certainly has not had a good impact on improving character values for students. The formulation of the problem in the research is whether the appreciation of class-based community-based weekend literature is effective in increasing the character values as well as the literary appreciation abilities of students of SD Pertiwi Makassar? This activity was carried out at Pertiwi Makassar Elementary School. The data analysis technique was used descriptively in the form of a presentation of each of the indicators studied. The results showed that the classroom-based literature appreciation activity was very effective in increasing the character values of students. This can be seen from the responses of students and parents as responding positively. Likewise there is a positive accompaniment impact for students because indirectly, students practice various forms of language skills such as discussion, presentation, lecture, listening, writing, and can improve democratic attitudes, scientific attitudes, and critical thinking.